Analisis dan Perancangan Sistem Repositori Tugas menggunakan Framework Website MVC Studi Kasus STT Terpadu Nurul Fikri - Andhito Revandra; Yekti Wirani (Jurnal Informatika Terpadu, 2020)
This research is developing an electronic documentation system to support the Academic archiving and documentation activities that already exist called the repository application developed with the framework yii2. The results of this study are the addition of the Home display feature so that there is a Document category menu to select the type of document chosen and a menu bar for document search. Testing results with black box testing obtained with 75% suitability and with UAT got 55.55% suitability. The courses at STT-NF itself are still interconnected between semesters, and some assignments in the previous semester are still needed. So to facilitate students in accessing assignments, a repository management system for the coursework was created to help STT-NF students manage online assignment archiving.